HUKUMAN TINDAK PIDANA KORUPSI DI INDONESIA DALAM PERSPEKTIF FIQH - Ahmad Edwar (Almarhalah, 2021)
Islamic Shari’ah functioned by God as a deterrent to evil. Jurisprudence of Jinayat in Islamic law recognizes three kinds of punishment for a crime committed by a person; Qishah, hudud and ta’zir. The determination of punishment is not merely a revenge, but rather a goal to create a deterrent effect or shock to create a calm and peaceful society situation as the message contained in the word hayah which means a peaceful life. This paper aims to reveal the concept of punishment in the crime of corruption in the eyewear of Jinayat jurisprudence. Through literature review it can be concluded that the sanction of corruption is ta’zir, which is adjusted with the judge’s decision based on the level of corruption that has been done. Sanctions in the form of ta’zir vary from mild to severe enough to recall corruption with a complex social impact. The ta’zir sanctions that can be given to the perpetrators of corruption are; Imprisonment, defamation, material fines to death penalty.Keywords: Fikh; Criminal Actions; Corruption; Sanctions; Ta’zir